Trabeculectomy augmentation in primary open-angle glaucoma: Mitomycin-C versus Ologen implant - Tamer I Salem (Delta Journal of Ophthalmology, 2015)
Introduction Trabeculectomy is the most commonly performed surgical intervention to reduce intraocular pressure (IOP) for medically uncontrolled glaucoma. Different augmentation procedures have been proposed to increase success rate and reduce postoperative complications. Purpose The aim of this study was to evaluate the results of different augmentation procedures used with trabeculectomy in patients with primary open-angle glaucoma. Patients and methods The study included 60 patients. Patients were randomly divided into three groups: the first group underwent trabeculectomy with low-dose mitomycin-C (MMC) (0.1 mg/ml); the second group underwent trabeculectomy with collagen matrix implant (Ologen) TM; and the third group underwent trabeculectomy with both low-dose MMC and Ologen implant. IOP was the primary outcome measure and the target level was set at less than 18 mmHg. Secondary outcome measures included bleb evaluation, number of glaucoma medications, and frequency of postoperative adjunctive procedures and complications. Results Postoperatively, there was a significant decrease in IOP in all studied groups when compared with their corresponding preoperative values, and there was no significant difference between the studied groups at any point of time except at 1 month, when there was a significant decrease in IOP in the MMC group compared with the Ologen or Ologen plus MMC groups. In addition, the Ologen plus low-dose MMC group had better bleb scoring. There was no significant difference between the groups as regards complications. The success was complete in 46 cases (76.7%), and qualified success was reported in 14 cases (23.3%). Complete success was equally reported in the MMC group and in the Ologen plus MMC group (85.0%), whereas it was 60.0% in the Ologen group. Conclusion Both MMC and Ologen appear to be safe, effective, and promising as augmentation procedures with trabeculectomy in patients with primary open-angle glaucoma.